Development and Validation of an Unethical Professional Behavior Tendencies Scale for Student Teachers - Wang, Jing; Wang, Xin-qiang; Li, Jia-yuan; Zhao, Cui-rong; Liu, Ming-fan; Ye, Bao-juan (Frontiers in Psychology, 2021)
Teacher’s unethical professional behaviors affect students’ physical and mental health. Prevention should start with student teachers, but empirical research is lacking in China. This study surveyed over 2,000 student teachers from China to examine the psychometric properties of a student teachers’ unethical professional behaviors tendencies scale which revised by primary and secondary school teachers’ unethical professional behaviors tendencies scale. Exploratory and confirmatory factor analysis confirmed that a bi-factor model fit the data best. The final student teachers’ unethical professional behaviors tendencies scale comprised four subscales, including a general factor (unethical professional behaviors) and four special factors (Perfunctoriness and Carelessness, Insults and Discrimination, Unfairness, Using Power for Personal Gain). The student teachers’ unethical professional behaviors tendencies scale correlated negatively with their professional ethical values and positively with perceived frequency of unethical professional behaviors of college teachers around them. The data supported the scale’s measurement invariance across gender, and male student teachers scored significantly higher on unethical professional behaviors tendencies than females. The findings suggest that the student teachers’ unethical professional behaviors tendencies scale is a useful instrument for assessing student teachers’ unethical professional behaviors in China.